2017
DOI: 10.1002/ca.22999
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the frontal sinus and its relationship with the orbital cavity

Abstract: The anatomy of the frontal sinus is highly variable and its variations affect the occurrence/course of pathological processes. We investigated its size and relationship to the orbit, searching for patterns that would allow it to be classified anatomically. Cone beam computed tomography was applied to 91 skulls (age range 21-86 years) to determine sinus height, width, length, and length of contact with the orbit in the coronal and sagittal planes. In addition, orbital roof pneumatization in the coronal plane wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…The variability of their patterns (i.e. configuration, shape, anatomical variations, dimensions) is wide (Szilvássy, 1982; Guerram et al ., 2014; Lund et al ., 2014; Choby et al ., 2018; Štoković et al ., 2018). Because these sinuses are encased in the solid frontal bone, they are usually preserved in archaeological contexts and we can evaluate them even if the overall preservation of skeletal remains is poor (Cameriere et al ., 2008; Goyal et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The variability of their patterns (i.e. configuration, shape, anatomical variations, dimensions) is wide (Szilvássy, 1982; Guerram et al ., 2014; Lund et al ., 2014; Choby et al ., 2018; Štoković et al ., 2018). Because these sinuses are encased in the solid frontal bone, they are usually preserved in archaeological contexts and we can evaluate them even if the overall preservation of skeletal remains is poor (Cameriere et al ., 2008; Goyal et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…6 The anatomical variations of the frontal sinus morphology have been reported in various populations worldwide. 1,[7][8][9][10][11][12] These studies have confirmed that climate and geography influence the frontal sinus morphology differences between the populations. In addition, few studies have demonstrated sexual dimorphism in frontal sinus anatomic variations.…”
Section: Introductionmentioning
confidence: 68%
“…An understanding of the anatomical variations in the orbit is clinically important as, for example, the wormian bones might simulate fractures on imaging of the orbit or may get dislodged during surgical manipulation causing injury to the nerves, blood vessels, and the eyeball [ 9 , 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%